A novel variable geometry turbine achieved by elastically restrained nozzle guide vanes. (August 2020) - Wang, Zhihui; Ma, Chaochen; Huang, Zhi; Huang, Liyong; Liu, Xiang; Wang, Zhihong
Variable geometry turbocharging is one of the most significant matching methods between turbocharger and engine, and has been proven to provide air boost for entire engine speed range as well as to reduce turbo-lag. An elastically constrained device designed for a novel variable geometry turbocharger was presented in this paper. The design of the device is based on the nozzle vane's self-adaptation under interactions of the elastic force by elastically restrained guide vane and the aerodynamic force from flowing gas. The vane rotation mechanism of the novel variable geometry turbocharger is different from regular commercial variable geometry turbocharger systems, which is achieved by an active control system (e.g. actuator). To predict the aerodynamic performance of the novel variable geometry turbocharger, the flow field of the turbine was simulated using transient computational fluid dynamics software combined with a fluid–structure interaction method. The results show that the function of elastically constrained device has similar effectiveness as the traditional variable geometry turbocharger. In addition, the efficiency of the novel variable geometry turbocharger is improved at most operating conditions. Furthermore, a turbocharged diesel engine was created using the AVL BOOST software to evaluate the benefits of the new variable geometry turbocharger. The proposed novel variable geometry turbocharger can effectively improve the engine performance at mid-high speeds, such that the maximum decrease of brake-specific fuel consumption reaches 17.91% under 100% load and 3600 r/min engine condition. However, the engine power and brake-specific fuel consumption decrease significantly at low engine speed conditions, and the decrease is more than 26% under 1000 r/min.